First-line chemoimmunotherapy and immunotherapy in patients with non-small cell lung cancer and brain metastases: a registry study - Brown, Lauren Julia; Khou, Victor; Brown, Chris; Alexander, Marliese; Jayamanne, Dasantha; Wei, Joe; Gray, Lauren; Chan, Wei Yen; Smith, Samuel; Harden, Susan; Mersiades, Antony; Warburton, Lydia; et al. (Frontiers in Oncology, 2024)
Introduction: Brain metastases commonly occur in patients with non-small cell lung cancer (NSCLC). Standard first-line treatment for NSCLC, without an EGFR, ALK or ROS1 mutation, is either chemoimmunotherapy or anti-PD-1 monotherapy. Traditionally, patients with symptomatic or untreated brain metastases were excluded from the pivotal clinical trials that established first-line treatment recommendations. The intracranial effectiveness of these treatment protocols has only recently been elucidated in small-scale prospective trials. Methods: Patients with NSCLC and brain metastases, treated with first-line chemoimmunotherapy or anti-PD-1 monotherapy were selected from the Australian Registry and biObank of thoracic cancers (AURORA) clinical database covering seven institutions. The primary outcome was a composite time-to-event (TTE) outcome, including extracranial and intracranial progression, death, or need for local intracranial therapy, which served as a surrogate for disease progression. The secondary outcome included overall survival, intracranial objective response rate (iORR) and objective response rate. Results: 116 patients were included. 63% received combination chemoimmunotherapy and 37% received anti-PD1 monotherapy. 69% of patients received upfront local therapy either with surgery, radiotherapy or both. The median TTE was 7.1 months (95% CI 4.9-9.3) with extracranial progression being the most common progression event. Neither type of systemic therapy or upfront local therapy were predictive of TTE in a multivariate analysis. The median OS was 17 months (95% CI 13-27). Treatment with chemoimmunotherapy was predictive of longer OS in multivariate analysis (HR 0.35; 95% 0.14 – 0.86; p=0.01). The iORR was 46.6%. The iORR was higher in patients treated with chemoimmunotherapy compared to immunotherapy (58% versus 31%, p=0.01). The use of chemoimmunotherapy being predictive of iORR in a multivariate analysis (OR 2.88; p=0.04). Conclusion: The results of this study of real-world data demonstrate the promising intracranial efficacy of chemoimmunotherapy in the first-line setting, potentially surpassing that of immunotherapy alone. No demonstrable difference in survival or TTE was seen between receipt of upfront local therapy. Prospective studies that are required to assist clinical decision making regarding optimal sequencing of local and systemic therapies.